كاریگه‌ریی شیعره‌كانی خیام له‌سه‌ر شیعره‌كانی گۆران - عزیز, سامان جلال; حمەکریم, سەبور عبدالکریم; محمود, ارکان عبدالله (Sulaimani Journal for Humanities, 2018)
Goran is a Kurdish poet and an educated. He lives between two world wars and after them. Omar Alkhayam is a Persian Poet. He was A philosopher and a mathematician and he lives between (1048-1131). He wrote poems in Rubbaei form which is consist of four lines. This thesis which entitled: “Influence Omar Alkayam's poem on Goran's Poem" is a comparative research between the two poets poem. According to the nature of the subject, the thesis contains: introduction, four chapters, conclusions, Arabic and English abstract, and a list of references. Chapter one: named ”Non continuous of life and its absurdist” it deals with comparing between the two poets poems. Also precisely we shed lighted on their deference. Chapter two: named” Epoch and era” it deals with comparing between their poems and their deference attitude about it. Chapter three: named” Fatalist of Human Being” it deals with comparing between their poems. Also precisely we shed lighted on their deference. Chapter Four: named” Death” in this chapter we showed some essential their deference attitudes about death. At the end of the thesis, the main conclusions resulted from this study are presented. This is followed by a list of references.